Deformation techniques for counting the real solutions of specific polynomial equation systems - Dratman, E. (2002)
We present a deformation technique which allows us to determine the number of real solutions of certain specific polynomial equation system. We apply this deformation technique in order to determine the number of stationary solutions of the semidiscretization of certain parabolic differential equations.